2020
DOI: 10.1021/acs.biomac.9b01644
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Chain Conformation and Bioactivities of Triple-Helix Polysaccharides

Abstract: Natural polysaccharides derived from renewable biomass sources are regarded as environmentally friendly and sustainable polymers. As the third most abundant biomacromolecule in nature, after proteins and nucleic acids, polysaccharides are also closely related with many different life activities. In particular, β-glucans are one of the most widely reported bioactive polysaccharides and are usually considered as biological response modifiers. Among them, β-glucans with triple-helix conformation have been the hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(74 citation statements)
references
References 240 publications
0
74
0
Order By: Relevance
“…The triple-helix β-glucans with high molecular weight show stronger anticancer properties [ 10 , 15 ]. Mushroom glucans often form intermolecular interactions yielding complex polymers that are difficult to isolate, but recent studies suggest a simple and effective procedure that allows to separate different glucan structures.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The triple-helix β-glucans with high molecular weight show stronger anticancer properties [ 10 , 15 ]. Mushroom glucans often form intermolecular interactions yielding complex polymers that are difficult to isolate, but recent studies suggest a simple and effective procedure that allows to separate different glucan structures.…”
Section: Resultsmentioning
confidence: 99%
“…Nitschke et al [ 29 ] found that Congo red binds only Congo red positive β-glucans with the triple-helix structures. However, it should be stressed that the triple helical structures of β-glucans are susceptible for conformation transition in some solvents and under some chemical and physical conditions like very high temperature [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations